2013
DOI: 10.1111/j.2047-2927.2013.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk and bone loss in men undergoing androgen deprivation therapy for non‐metastatic prostate cancer: implementation of standardized management guidelines

Abstract: SUMMARYOur objective was to evaluate the effectiveness of implementing standardized guidelines to mitigate metabolic and bone side effects of androgen deprivation therapy (ADT) in men with non-metastatic prostate cancer. We conducted a 2-year prospective cohort study at a tertiary referral teaching hospital. Overall, 236 men (mean age 69.8 AE 7.1) commencing ADT for non-metastatic prostate cancer attended a baseline clinic visit between 2007 and 2011, and 153 men were eligible for follow-up after 2 years of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 30 publications
2
59
0
Order By: Relevance
“…The lifetime risk of bone fractures secondary to osteoporosis is B20%. 14 Cheung et al 15 showed in an audit of 236 men that, at initiation of ADT, 11% had osteoporosis and 40% osteopenia. In addition, 61% of those with osteoporosis were unaware of it.…”
Section: Clinical Predisposing Factors For Bone Loss and Osteoporosismentioning
confidence: 99%
“…The lifetime risk of bone fractures secondary to osteoporosis is B20%. 14 Cheung et al 15 showed in an audit of 236 men that, at initiation of ADT, 11% had osteoporosis and 40% osteopenia. In addition, 61% of those with osteoporosis were unaware of it.…”
Section: Clinical Predisposing Factors For Bone Loss and Osteoporosismentioning
confidence: 99%
“…To date, only one set of guidelines [56] , which focussed on bone and metabolic outcomes of ADT, has been implemented and evaluated [220] . In a two year prospective study, 236 men with PCa commencing ADT attended a clinic visit and received diet and lifestyle advice with overweight and obese men offered referral to a dietitian [220] .…”
Section: Potential Interventions To Improve Muscle Fat and Performanmentioning
confidence: 99%
“…As many as 40% of patients suffer from osteopenia, and 11% -from osteoporosis [29], even before the beginning of hormonal treatment. Prostate cancer usually affects older patients and the loss of bone mass is related to the normal physiological ageing process.…”
Section: Osteoporosismentioning
confidence: 99%